The Quality of Rhyme and Rhythm in Song Lyric Translation - Fitri, Aulia; Dewi, Haru Deliana; Hidayat, Rahayu Surtiati (Paradigma: Jurnal Kajian Budaya, 2022)
This research is a development of Low’s theory (2008) on assessing the quality of song lyric translation based on its translation method. The objective of the study is to discover the quality of rhyme and rhythm of song lyrics in the album We Love Disney which have been translated from English to Indonesian. Therefore, this study focuses on the quality of rhyme and rhythm of the translation because these elements are significant parts of the songs. Low’s theory has been applied in the present study to measure the song lyric translation quality using three translation methods: communicative, free, and semantic methods. The study employs a qualitative approach through comparative analysis. Data in the analysis are the song lyrics and their translation, and their rhymes and rhythms. The values of the rhyme and rhythm in the translations were obtained from the comparative analysis. The findings reveal that song lyrics translated using the communicative translation method have a higher rhyme value than the original song lyrics; in contrast, the lyrics translated using a free method yield a rhyme value with a considerable difference. The assessment of rhythm reveals that a song translated using the free method shows a substantial difference in value compared to translations using the other methods. KEYWORDS